2012
DOI: 10.14245/kjs.2012.9.3.165
|View full text |Cite
|
Sign up to set email alerts
|

A PET/CT-based Morphometric Study of Spinal Canal in Korean Young Adults: Anteroposterior Diameter from Cervical Vertebra to Sacrum

Abstract: ObjectiveTo establish normative data for spinal canal AP diameter from cervical vertebra to sacrum in the Korean young and to assess the exposed spinal canal after laminectomy which was related with restenosis by post-laminectomy membrane formation.MethodsFrom PET/CT, axial bone-window CT of 83 young adults (20-29 years) were obtained, and we measured AP diameters of C3, C5, C7, T1, T4, T8, T12, L1, L3, L5 and S1. We also measured exposed AP diameter of C3, C5, C7, T1 and T2 above imaginary line for laminectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…They found that average thoracic diameters at T1, T8 and T12 were 16.1, 14.6, and 16.7 mm, respectively. As expected, average spinal cord diameters were smaller on AP diameter with measurements from T1 to T12 ranging from 5 to 9 mm, with the spinal cord diminishing in size from T1 to T8 and increasing in size from T8 to T12 26 . Overall, spinal canal stenosis is defined by having a canal AP diameter of <10 mm, with a critical “pathologic” threshold of 5 mm 26,27 …”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…They found that average thoracic diameters at T1, T8 and T12 were 16.1, 14.6, and 16.7 mm, respectively. As expected, average spinal cord diameters were smaller on AP diameter with measurements from T1 to T12 ranging from 5 to 9 mm, with the spinal cord diminishing in size from T1 to T8 and increasing in size from T8 to T12 26 . Overall, spinal canal stenosis is defined by having a canal AP diameter of <10 mm, with a critical “pathologic” threshold of 5 mm 26,27 …”
Section: Discussionsupporting
confidence: 53%
“…To ensure adequate canal diameter for SCS paddle lead placement, we examined studies that help define average thoracic canal, average spinal cord diameter, and critical stenosis. Sagittal AP diameter of the spinal canal has been shown to be the only measurement that correlates well with cross‐sectional area and is a good indicator of spinal canal size 26,27 . Fradet et al 27 reported variation among subject of up to 150% in both spinal canal diameter and spinal cord diameter using high‐resolution MRI, reporting overall thoracic spinal canal diameters (T1, T8, and T12) from various studies showed ranges from 15.0 to 16.1 mm, 14.6 to 16.6 mm, and 16.7 to 17.2, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average CT-VBD gradually decreased from T1 to T4 and increased from T5 to L5. Singh et al [26] Kang M S et al (2012) [39] reported in the thoracic spine, the AP diameter of neural canal gradually decreased from T1 (16.1±1.2mm) to T8 (14.6±1.3mm) and increased to T12 (16.7±1.2mm). Berry et al reported AP diameters of neural canal 15.0mm at T2, 16.6 mm at T7, 17.2 mm at T12.…”
Section: Discussionmentioning
confidence: 93%
“…2,4,7,11 However, comparison of published data reveals that the range of variation in the reported sagittal diameter is considerable. 1,[3][4][5][6]10 Those diversity is partly due to the variation in the radiographic technique (focus-to-film distance) and variation in the body build of the subjects (affecting the object-to-film distance).…”
Section: Discussionmentioning
confidence: 99%